2003
DOI: 10.1021/ja036357v
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Sample-Mixing Technique for Transient NMR and Photo-CIDNP Spectroscopy:  Applications to Real-Time Protein Folding

Abstract: We describe the development and application of a novel rapid sample-mixing technique for real-time NMR (nuclear magnetic resonance) spectroscopy. The apparatus consists of an insert inside a conventional NMR tube coupled to a rapid injection syringe outside the NMR magnet. Efficient and homogeneous mixing of solutions in the NMR tube is achieved with a dead time of tens of milliseconds, without modification of the NMR probe or additional hardware inside the magnet. Provision is made for the inclusion of an opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
104
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 48 publications
1
104
0
2
Order By: Relevance
“…The triggering of kinetic reactions can be achieved either by a sudden change of the protein state itself, e.g., by a photo-induced excitation or cleavage of chemical bonds (16,17), or by a change of environment, such as the solvent composition, temperature, or pH (4,18). Here, we opted for an initiation of the reaction by an abrupt change in the solvent conditions achieved by rapid mixing of two solutions inside the NMR magnet (5,19). The fast mixing device used for this work (SI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The triggering of kinetic reactions can be achieved either by a sudden change of the protein state itself, e.g., by a photo-induced excitation or cleavage of chemical bonds (16,17), or by a change of environment, such as the solvent composition, temperature, or pH (4,18). Here, we opted for an initiation of the reaction by an abrupt change in the solvent conditions achieved by rapid mixing of two solutions inside the NMR magnet (5,19). The fast mixing device used for this work (SI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently developed NMR techniques to characterize aromatic side chains in transient, kinetic intermediate species present in real-time protein folding experiments (13,14) or in partially folded states that are stable under equilibrium conditions (15,16). To circumvent the difficulties in studying such states directly, we have shown that magnetization transfer from the partially folded state to the N state by rapidly refolding the protein can, in principle, yield structural information on the former from the well resolved spectrum of the latter (14)(15)(16).…”
mentioning
confidence: 99%
“…To circumvent the difficulties in studying such states directly, we have shown that magnetization transfer from the partially folded state to the N state by rapidly refolding the protein can, in principle, yield structural information on the former from the well resolved spectrum of the latter (14)(15)(16). However, to carry out such experiments successfully, it is essential that refolding takes place faster than nuclear spin-lattice relaxation.…”
mentioning
confidence: 99%
“…[33][34][35] The combination of atomic resolution applicable to relatively fast kinetics cannot be achieved by any other biophysical method. Dynamic events of biomacromolecules in this time range are large scale conformational transitions, folding events (for proteins) and macromolecular assembly.…”
mentioning
confidence: 99%
“…82 For the latter experimental setup, there are also two possibilities amenable: in the first method one solution is injected into another inside the NMR tube, so that after the injection the turbulences cause homogeneous and rapid mixing. 33 The second method uses mobile separators of the two solutions that can be removed rapidly and thereby facilitate mixing. 83 For the very early mixing instruments, already after a dead time of s dead $ 0.2 s a spectrum with sufficient resolution could be recorded.…”
mentioning
confidence: 99%